Age and sex‐related differences in risk factors for elderly suicide: Differentiating between suicide ideation and attempts. (2nd October 2017) - Lee, Hyuk; Seol, Ki Ho; Kim, Jun Won
Abstract : Objective: The purpose of this study was to analyze the age and sex‐related differences in socio‐demographic factors that influence suicide ideation and attempts in the elderly. Methods: The total number of subjects was 93 151, of whom 8441 belonged to the high suicide‐risk group (2064 male; 6377 female). Following this identification, we investigated their socio‐demographic information, health status, and depressive symptoms, which might have influenced their suicide ideation and attempts. Results: Residence in an urban area was identified as a risk factor for both male and female elderly in their 60s and 70s and female elderly in their 80s. Marital status showed a different influence on suicide ideation depending on age and sex. A negative perception of one's own health status was a significant risk factor that increased the likelihood of suicide ideation in all ages, except the female elderly in their 60s. No factor was identified that significantly influenced suicide attempts in the male elderly. However, in the female elderly, residence in an urban area and a negative perception of one's own health status were identified as significant risk factors. Conclusions: This study revealed that factors known to influence suicide ideation in the elderly from previous studies, such as residence area, separation from a spouse, education level, religion, and drinking, show changed influence as the elderly reach their 70s and 80s. However, a negative perception of one's own health status was a risk factor that encompassed most ages and sexes.